If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = 2p + 4 Reorder the terms: 10 = 4 + 2p Solving 10 = 4 + 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. 10 + -2p = 4 + 2p + -2p Combine like terms: 2p + -2p = 0 10 + -2p = 4 + 0 10 + -2p = 4 Add '-10' to each side of the equation. 10 + -10 + -2p = 4 + -10 Combine like terms: 10 + -10 = 0 0 + -2p = 4 + -10 -2p = 4 + -10 Combine like terms: 4 + -10 = -6 -2p = -6 Divide each side by '-2'. p = 3 Simplifying p = 3
| Y=12-6x/-2 | | 8(7-y)=-14 | | C/4=8.96 | | Y-32x+11=0 | | 3a+3z= | | (d+3d)-(-d+2)d=5 | | 7.0x-3x=1 | | 10/(10x-1) | | (6c-4)-(c-3)c=3 | | 8+2n=22 | | 7c-10c+8c-c-c= | | 7a+8=5a-2 | | 2(x-6)-1=5-(4x+2) | | 3h-4h=13 | | 5=17-6t | | B-(2b+1)b=5 | | 8+n=22 | | 4=12-2s | | 20y+9=4(5y+1) | | 5=7-2p | | 2x^5-12x^4+18x^3=0 | | 315/45 | | 2x-46+x=30-7 | | X/4=10.6 | | 9(3-2x)=3(10-8x) | | 0=32x+11 | | 4x+(x-0.5x)=36 | | 21y+4=4(5y+1) | | 5(3x-1)=56 | | 8x+x-6x-4x-5x= | | 6=3b-9 | | -29=5(2d-1)+2a |